The Thermodynamic Stability Theory of Non-Equilibrium States - Glansdorff, P. (1974)
The paper by J. Keizer and R. F. Fox entitled “Qualms Regarding the Range of Validity of the Glansdorff-Prigogine Criterion for Stability of Non-Equilibrium States” [(1974) Proc. Nat. Acad. Sci. USA 71, 192-196.] is shown to be based on a misunderstanding of the work of the Brussels group. In order to avoid further confusion, we summarize the formulation of the stability criterion in accordance with our published work. The differences with the presentation by Keizer and Fox are pointed out and it is shown that, when correctly applied, our approach does not lead to any contradiction with other methods available for studying stability.